Perbedaan pengetahuan dan praktik pemberian makan serta perkembangan anak 6-24 bulan pada ibu usia remaja dan dewasa - Rachmawati Widyaningrum; Detty Siti Nurdiati; Indria Laksmi Gamayanti (Jurnal Gizi Klinik Indonesia, 2016)
Background: Preparing quality human resource for the future, children are being the most attention of the growth and development optimally. Critical aged of them is 0-2 years old. Pregnancy and giving birth on adolescence are still being the factors. Knowledge and feeding practice are also factors being the basic need for children development optimally.Objective: To know the difference between knowledge, feeding practice, and children development aged 6-24 months on adolescent and adult mother in Kasihan Primary Health Care, Bantul district, Yogyakarta.Method: This research was observational with a cross-sectional design. It held on July -September 2015 in work area of Kasihan subdistrict, Bantul district, Yogyakarta. Population defined as mother aged 15-40 years that lives in Kasihan subdistrict. The sample was taken using nonprobability consecutive technique sampling. It was got 66 children aged 6-24 months old with no having congenital defects, no following special development stimulation program,  and being able and want to follow this research as inclusion criteria. In this research, a mother was measured of knowledge level and feeding practice to her child, even though the child was measured off his/her development using BSID III. Data were analyzed using Chi-Square.Results: Adolescent mothers had a significantly larger proportion of children experiencing developmental disorders and feeding practices are less good compared with adult mothers.Conclusion: Adult mother has better knowledge and feeding practice than adolescent mothers. Adult mother also has a child with better developmental status than adolescent mothers.